2017
DOI: 10.1021/acs.iecr.7b01181
|View full text |Cite
|
Sign up to set email alerts
|

Hexavalent Actinide Extraction Using N,N-Dialkyl Amides

Abstract: Recently, efforts towards closing the nuclear fuel cycle have considered oxidizing americium to a hexavalent, linear-dioxo cation for co-recovery with hexavalent U, Np, and Pu from molar nitric acid using solvating extraction ligands such as tri-n-butyl phosphate or diamyl amylphosphonate. This work assesses solvent extraction recovery of sodium bismuthate oxidized americium by N,N-di-(2-ethylhexyl)butyramide (DEHBA), N,N-di-(2-ethylhexyl)isobutyramide (DEHiBA), and N,N-dihexyloctanamide (DHOA). Extraction eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 21 publications
2
37
1
Order By: Relevance
“…[9][10][11][12] Recent studies have demonstrated 5f element group co-extraction of U(VI), Pu(VI), Np(VI), and Am(VI) using numerous extractants. [13][14][15] These studies demonstrate a simplified pathway to separate americium from the trivalent lanthanides and curium; widely regarded as one of the most challenging separations in radiochemistry.…”
Section: Introductionmentioning
confidence: 87%
“…[9][10][11][12] Recent studies have demonstrated 5f element group co-extraction of U(VI), Pu(VI), Np(VI), and Am(VI) using numerous extractants. [13][14][15] These studies demonstrate a simplified pathway to separate americium from the trivalent lanthanides and curium; widely regarded as one of the most challenging separations in radiochemistry.…”
Section: Introductionmentioning
confidence: 87%
“…The fitting results calculated from the Langmuir, Freundlich, and D-R isotherm models are summarized in Tables 2 and 3 5) obeys the Langmuir isotherm model (R 2 > 0.99) by comparing the R 2 parameters of Langmuir and Freundlich isotherm models, which suggested that the adsorption of U(VI) onto the adsorbents follows the monolayer adsorption manner. 14 The theoretical maximum adsorption capacity are about 35.4, 88.1, 90.3, and 131.9 mg/g for PANI, PA-PANI-1, PA-PANI-3, and PA-PANI-5, respectively.…”
Section: Methodsmentioning
confidence: 84%
“…Several methods have been demonstrated to remove U­(VI) from aqueous solution, for instance, chemical precipitation, ion exchange, adsorption, and solvent extraction. Among these methods, the adsorption method has been widely studied owing to its advantages of simple operation, high adsorption capacity, high selectivity, and ease of repetitive use. Various adsorbents have been reported for the elimination of U­(VI), such as polymers (polyaniline, chitosan bearing α-aminophosphonate and polypyrrole), carbon material (graphene oxide, carbonaceous nanofibers), , metal oxide (MnO 2 ), and metal–organic frameworks …”
Section: Introductionmentioning
confidence: 99%
“…The rejection coefficient of Eu 3+ is low at 1.3%. These results give rise to a Am(VI)/Eu(III) separation factor of 873 that is significantly higher than those of all other americium oxidation associated separation techniques [20][21][22][23][24][25][26][27] (Fig. 4c).…”
Section: Mainmentioning
confidence: 81%